2015
DOI: 10.1111/tra.12271
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Morphometry Points to a New Role for LAMTOR2 in Regulating the Endo/Lysosomal System

Abstract: The late endosomal adaptor protein LAMTOR2/p14 is essential for tissue homeostasis by controlling MAPK and mTOR signaling, which in turn regulate cell growth and proliferation, migration and spreading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 92 publications
(147 reference statements)
7
40
0
Order By: Relevance
“…It is unclear how the assembly of BORC is regulated within the cell or if this complex regulates mTORC1, but the authors imply that Ragulator interacts with BORC subunits (Pu et al, 2015), which would indicate a role for the c17orf59-Ragulator complex in lysosomal positioning as a part of BORC. This is consistent with literature that Ragulator components are important for maintaining endolysosomal morphology and biogenesis (Teis et al, 2006; Nada et al, 2009; Takahashi et al, 2012; Vogel et al, 2015) and consistent with our observed alterations in lysosomal staining in cells that overexpress c17orf59 (Figure 4E and Figure 5B). It is possible that Ragulator binds to c17orf59 and BORC in a Rag- and mTORC1-independent manner to control endosome and lysosome morphology.…”
Section: Discussionsupporting
confidence: 93%
“…It is unclear how the assembly of BORC is regulated within the cell or if this complex regulates mTORC1, but the authors imply that Ragulator interacts with BORC subunits (Pu et al, 2015), which would indicate a role for the c17orf59-Ragulator complex in lysosomal positioning as a part of BORC. This is consistent with literature that Ragulator components are important for maintaining endolysosomal morphology and biogenesis (Teis et al, 2006; Nada et al, 2009; Takahashi et al, 2012; Vogel et al, 2015) and consistent with our observed alterations in lysosomal staining in cells that overexpress c17orf59 (Figure 4E and Figure 5B). It is possible that Ragulator binds to c17orf59 and BORC in a Rag- and mTORC1-independent manner to control endosome and lysosome morphology.…”
Section: Discussionsupporting
confidence: 93%
“…HeLa and MEF formed strictly flat, non‐confluent monolayers, CaCo2 grew as confluent, up to ≈20 μm high, polarized monolayers. HPF was performed as previously described in detail …”
Section: Resultsmentioning
confidence: 82%
“…; 5% vol/vol) and methanol (1% vol/vol) gave consistently the best results. As judged from standard 100 nm thin sections the cellular fine structure of these FS‐RH samples appeared generally well preserved (eg, Figures and AB), quite similar to classical FS samples (eg, Reference : Figure ; Ref. : Figures B and 4G).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Repeated fusions of endosomes with lysosomes generate endolysosomes with degradation of the intralumenal vesicles harboring internalized receptors (28,(92)(93)(94). The generation of multivesicular endosomes has been implicated in signal transmission, especially for Wnt signaling.…”
Section: Maturation Of Multivesicular Endosomes To Lysosomesmentioning
confidence: 99%